1996
DOI: 10.1590/s0004-282x1996000100007
|View full text |Cite
|
Sign up to set email alerts
|

High doses of carbamazepine for refractory partial epilepsy

Abstract: Forty-eight patients with partial seizures were analysed during treatment with 1200 mg/d or more of carbamazepine (CBZ). Thirty-three were on monotherapy and fifteen on polytherapy. The other drugs were kept unchanged in the patients on polytherapy. The dose of CBZ was increased if no control was observed and the patient had no side effects. The doses used ranged between 1200 and 1900 mg/day (1200 mg/day, n=18; 1300mg/day, n=1; 1400 mg/day, n=7; 1600 mg/day, n=9; 1700 mg/day, n=4; 1800 mg/day, n=8; 1900 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The following ASMs were specifically evaluated as an intervention by one study reporting clinical outcomes (see Table 3 ): CBZ, 13 cenobamate, 14 clobazam (CLB), 15 eslicarbazepine (ESL), 16 lacosamide (LCS), 17 levetiracetam (LEV), 18 lamotrigine (LTG), 18 perampanel (PER), 19 pregabalin (PGB). 20 Clinical outcomes of specific combinations of ASMs, including CBZ/valproic acid (VPA) compared to CBZ monotherapy 21 and VPA/LTG compared to VPA and/or LTG monotherapy, 22 were evaluated in one study each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following ASMs were specifically evaluated as an intervention by one study reporting clinical outcomes (see Table 3 ): CBZ, 13 cenobamate, 14 clobazam (CLB), 15 eslicarbazepine (ESL), 16 lacosamide (LCS), 17 levetiracetam (LEV), 18 lamotrigine (LTG), 18 perampanel (PER), 19 pregabalin (PGB). 20 Clinical outcomes of specific combinations of ASMs, including CBZ/valproic acid (VPA) compared to CBZ monotherapy 21 and VPA/LTG compared to VPA and/or LTG monotherapy, 22 were evaluated in one study each.…”
Section: Resultsmentioning
confidence: 99%
“… 23 , 24 , 25 , 26 , 27 , 29 , 31 , 32 Additionally, eight studies reported if seizure frequency was increased or exacerbated. 16 , 19 , 21 , 28 , 29 , 34 Sixteen studies addressed safety outcomes, 14 , 15 , 16 , 17 , 19 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 36 , 38 , 39 while seven studies reported plasma concentrations of the study drug 13 , 24 , 26 , 27 and/or all ASMs taken by patients. 22 , 28 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations